Bulk passive sensorless sorting of complex cylindrical components with internal features and symmetrical external tapers - Toby Williams; Kaddour Bouazza-Marouf (2022)
In robotic assembly, manipulators can be used extensively to undertake all the different facets of the process, however, this can be expensive and space inefficient. Instead, reduced intricacy in sensing and control (RISC) can be adopted involving minimal use of manipulators with parts of the process undertaken using passive methods. A novel tooling method has been developed to passively orientate complex shaped cylindrical components with symmetrical external tapers in bulk transit. The design of the tooling is component specific, however, this method can be applied to generic components. This technique has been successfully tested in an industrial assembly system